Sexual Activity as a Risk Factor for the Spontaneous Rupture of Cerebral Aneurysms. (June 2016) - Blanke-Roeser, Constantin; Matschke, Jakob; Püschel, Klaus
Abstract : Abstract: Subarachnoid hemorrhages from ruptured cerebral aneurysms have a high clinical relevance and often lead to death. Approximately 2% to 5% of the people worldwide, even of younger age, are said to have aneurysms at cerebral arteries. In many cases, they remain clinically unapparent for decades. However, there are numerous risk factors for the rupture of an aneurysm, including temporary raises of the blood pressure. Such changes of the blood pressure can be induced even by several everyday behaviors. For example, any sort of sexual activities may cause extensive raises of the blood pressure because of several physical and psychological factors. The term "sexual activity" covers sexual intercourse as well as masturbation. In this article, the remarkable case of a 24-year-old woman with a ruptured cerebral aneurysm in the context of masturbation is presented. It is discussed with respect to the possible pathophysiological effects of sexual activity on cerebral aneurysms.